Life Cycle UI with ex-ante Heterogeneous Workers - Simon Heiler (ZBW - Leibniz Information Centre for Economics, 2021)
The incentives to search for employment vary systematically over the life cycle and with idiosyncratic productivity. These variations should be accounted for when designing UI policy. Using a life cycle model with endogenous human capital accumulation and permanent differences in worker productivity, I assess the welfare implications from optimally setting effective UI replacement rates. Welfare gains are sizeable, both absolute and relative to the size of the program, amounting to up to 0.7% of consumption in all periods and states or roughly 30% of the size of the UI program. Moreover, I demonstrate that the entire gains from conditioning replacement rates on age only and about three quarters of the welfare gains from conditioning on age and productivity can be generated by a simple and robust implementation inspired by the current U.S. UI system, featuring only a constant replacement rate, a benefit floor, and a benefit cap.
Keywords: E24; E21; J24; J64; 330